Water balance evaluation and regularization of Albanian rivers basins - Pano, Niko, author; Avdyli, Bardhyl, author; Bukli, Marenglen, author; Gjoka, Koco, author; Colorado State University, publisher (Colorado State University. Libraries, 2006)
Albanian river basin is one of the main and most complicated natural territories in Europe: mountainous regions of an average altitude of 785m above the sea level, particular littological structure with an important cal care formation, typical Mediterranean climate regime, etc. This basin is 43 305km2, where 28 500km2 is inside the Albanian state and the rest outside it (Greece, FYROM, Kosovo, Monte Negro). Albanian catchments area water discharges into Adriatic and Ionian Seas. In this paper it is attempted to present a general evaluation of the water balance in the Albanian river system, including regionalization of the catchment's area of this system, according to the correspondent types of the water balance.
Hydrology days 2006
AGU hydrology days 2006
2006 annual AGU hydrology days was held at Colorado State University on March 20 - March 22, 2006.
Keywords: water balance components; potential and real evatranspiracion; global territory humidity; rationalization